Pengembangan Aplikasi Pencarian dan Penawaran Kerja Paruh Waktu untuk Usaha Mikro, Kecil, dan Menengah (UMKM) berbasis Progressive Web App (Studi Kasus Kota Malang) - Muhammad Avied Bachmid; Mahardeka Tri Ananta; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
MSME companies in Malang City often employ their employees on part-time contracts, mainly due to difficulties in obtaining capital and the increasing number of students who are ready to work part-time. For students, working part time is a way to gain work experience as well as extra pocket money. So far, the MSME companies employee recruitment process still relies on forums on social media such as Facebook and often experiences difficulties due to the limitations of the job vacancy forums, such as poor relevance, no templates for job postings, and rare information updates. To overcome this problem, researchers developed a part-time job search and offer application called Jobhere which was developed with progressive web app technology. The Jobhere app was developed using the SDLC waterfall model. The use of the waterfall model is because the functional requirements of the system have been defined at the beginning of development and there is no need for iterations and changes in requirements.